2007
DOI: 10.1051/ebr:2007032
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the potential of herbivorous insect gut bacteria to develop competence for natural transformation

Abstract: Whereas the capability of DNA uptake has been well established for numerous species and strains of bacteria grown in vitro, the broader distribution of natural transformability within bacterial communities remains largely unexplored. Here, we investigate the ability of bacterial isolates from the gut of grass grub larvae (Costelytra zealandica (White); Coleoptera: Scarabaeidae) to develop natural genetic competence in vitro. A total of 37 mostly species-divergent strains isolated from the gut of grass grub lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Although some DNA survived in laboratory-created environments that simulated human or animal gastrointestinal tracts, complementary research has concluded that the likelihood of functioning DNA being taken up by bacteria in the human or animal gut is extremely low and will be dependent upon rDNA and the chromosomes of any naturally competent bacteria in the gut sharing regions of identical sequences (Flint et al 2002;Nordgård et al 2007). Similar recent studies with insects (Brinkmann and Tebbe 2007; Ray et al 2007) also support this conclusion. Thus, breakdown of DNA in the gut, combined with the breakdown of the DNA due to food processing, reduces the risk of dissemination (Van den Eede et al 2004).…”
Section: Horizontal Gene Transfermentioning
confidence: 81%
“…Although some DNA survived in laboratory-created environments that simulated human or animal gastrointestinal tracts, complementary research has concluded that the likelihood of functioning DNA being taken up by bacteria in the human or animal gut is extremely low and will be dependent upon rDNA and the chromosomes of any naturally competent bacteria in the gut sharing regions of identical sequences (Flint et al 2002;Nordgård et al 2007). Similar recent studies with insects (Brinkmann and Tebbe 2007; Ray et al 2007) also support this conclusion. Thus, breakdown of DNA in the gut, combined with the breakdown of the DNA due to food processing, reduces the risk of dissemination (Van den Eede et al 2004).…”
Section: Horizontal Gene Transfermentioning
confidence: 81%
“…The occurrence of conjugal plasmid transfer and transduction was also observed in the flea and house fly gut (Hinnebusch et al, 2002; Petridis et al, 2006; Akhtar et al, 2009). An assessment of natural transformability of bacteria in the insect gut, however, failed to detect any transformation event, even with the use of A. baylyi strain BD413 as a recipient (Ray et al, 2007). …”
Section: Hgt In Natural Ecosystemsmentioning
confidence: 99%
“…The spread of transgenic plant DNA has been observed from decaying leaves, by simulated rainwater, in field plots, from roots, and via pollen (21,22). While efforts to detect HGT to A. baylyi in the gastrointestinal tracts of insects and animals were unsuccessful, digested transgenic plant tissue in insect fecal matter remains capable of transforming A. baylyi (23)(24)(25)(26). These studies inform continued assessment of HGT and provide insights into ways to design genetically modified organisms to decrease the risk of transgene dissemination.…”
Section: Monitoring Horizontal Gene Transfermentioning
confidence: 99%